Segment duration in Danish words in dependency on higher level phonological units - Fischer-Jørgensen, Eli (Annual Report of the Institute of Phonetics University of Copenhagen, 1982)
This paper presents data concerning differences in segment duration in Standard Danish due to syllable number, position in the utterance and (based on a very restricted material) syntactic boundaries and word boundaries. It is shown that the tendency to shortening of stressed vowels according to number of following syllables which has been found in many languages, is not valid for Danish, which, on the contrary, has vowel lengthening in disyllables of the type CVCə compared to monosyllables. The historical and dialectal background of this phenomenon is discussed. It is further shown that Danish has final lengthening, although of less magnitude than e.g. English, and that word boundaries seem to be of limited importance, except for the vowel lengthening in disyllables.